Effect of high-pressure homogenization on stability of emulsions containing zein and pectin - Maneerat Juttulapa; Suchada Piriyaprasarth; Hirofumi Takeuchi; Pornsak Sriamornsak (Elsevier, 2017)
The aim of this study was to investigate the effect of high-pressure homogenization on the droplet size and physical stability of different formulations of pectin-zein stabilized rice bran oil emulsions. The obtained emulsions, both before and after passing through high-pressure homogenizer, were subjected to stability test under environmental stress conditions, that is, temperature cycling at 4 °C/40 °C for 6 cycles and centrifugal test at 3000 rpm for 10 min. Applying high-pressure homogenization after mechanical homogenization caused only a small additional decrease in emulsion droplet size. The droplet size of emulsions was influenced by the type of pectin used; emulsions using high methoxy pectin (HMP) were smaller than that using low methoxy pectin (LMP). This is due to a greater emulsifying property of HMP than LMP. The emulsions stabilized by HMP-zein showed good physical stability with lower percent creaming index than those using LMP, both before and after passing through high-pressure homogenizer. The stability of emulsions after passing through high-pressure homogenizer was slightly higher when using higher zein concentration, resulting from stronger pectin-zein complexes that could rearrange and adsorb onto the emulsion droplets.